Nitrification and urease inhibitors reduce gaseous N losses and improve nitrogen use efficiency in wheat exposed to elevated CO2 and temperature - Chakrabarti, Bidisha; Bhatia, Arti; Sharma, Shikha; Tomer, Ritu; Sharma, Abhilasha; Paul, Ankita; Kumar, Vinod; Sutton, Mark A. (Frontiers in Sustainable Food Systems, 2024)
IntroductionClimate change significantly impacts food production by influencing crop growth and soil processes. Rising atmospheric CO2 levels and temperatures may affect reactive nitrogen losses from cultivated soils. This study aimed to quantify the effects of nitrification and urease inhibitors on reactive nitrogen losses from wheat soils in the context of elevated CO2 and temperature interactions.MethodsAn experiment was conducted in open top chambers for two consecutive years to quantify the effect of nitrification and urease inhibitors on ammonia (NH3), and nitrous oxide (N2O) emissions in wheat under elevated carbon dioxide (EC), elevated temperature (ET) and their interaction (ECT). The carbon dioxide (CO2) concentration ranged from 552 to 568 ppm in the EC treatment, while the average temperature was 2.1–2.5°C higher in ET treatment than ambient (AMB).Results and discussionThe N2O–N emission increased under ECT than ambient. Use of neem oil coated urea (NOCU) reduced the N2O–N emission by 10.3%, whereas, Limus coated urea reduced N2O–N emission by 14% as compared to prilled urea treatment under ECT. NH3–N emission from wheat soil also increased under ECT treatment as compared to AMB. Application of N through Limus, reduced NH3–N emission from wheat by 35.7–36.8% when compared with NH3–N emission from prilled urea ECT condition. Elevated temperature reduced grain weight by 7.6%. The grain N content reduced by 10.9% with prilled urea under ECT. The application of NOCU and Limus increased grain N by 6 and 9%, respectively, as compared to urea under ECT interaction. The application of nitrification and urease inhibitors may reduce reactive nitrogen losses and enhance nitrogen use efficiency under future climatic conditions.